Pengaruh Spa Kaki Diabetik Terhadap Kualitas Tidur Dan Sensitivitas Kaki Penderita Diabetes Mellitus Tipe 2 - Wardani, Erika Martining (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2019)
Introduction: Diabetes mellitus (DM) is a chronic disease that is a serious health problem in the world. A common problem in DM patients is sleep disturbance and a decrease in leg sensitivity that can be affected by less than optimal blood circulation, leading to neuropathy to diabetic ulcers. The prevalence of neuropathy in type 1 diabetes ranged between 8-54% and in type II DM 13-46%. Efforts to increase sleep quality the sensitivity of the foot and so that no complications can occur with complementary treatment with Diabetic Foot SPA. The aim of this study was to determine the effect of Diabetic Foot SPA on sleep quality and foot sensitivity in type 2 diabetes mellitus. Methods: This study used pre-experimental design with pre- and post-test design. The research sample was 60 respondents with type 2 diabetes mellitus who were determined by simple random sampling technique. Before and after the intervention of Diabetic Foot SPA for 3 days in a row was done sleep quality and leg sensitivity. Data analysis technique using Wilcoxon test. Result: The results showed after intervention of Diabetic Foot SPA there was a significant increase in sleep quality (p value 0,001) and sensitivity of the foot (p value 0,000). Conclusion: Foot reflexology therapy therapy can be applied to increase sleep quality and reduce the risk of neuropathy and than can prevent complications that result in diabetic ulcers or amputations. Keywords: Diabetic Foot SPA, Sleep Quality, Foot Sensitivity, Diabetes Mellitus Type 2